The Improvement of Human Resource Quality to Face the Transformation of Maritime Transportation in Support of National Defense at Sea - Dharma, Ricky Tri; Hermawan, Teddie Bernard; Wiwit, Hari (AGUSPATI Research Institute, 2024)
— The Industrial Revolution 4.0 has the potential to disrupt all lines of business, including the need for labour. Meanwhile, the vast potential of Indonesia's port and shipping industry, with 636 existing ports and 1,321 new ports, will require human resources with medium and high-level skills. The Industrial Revolution 4.0, which integrates Cyber Physical System (CPS) and the Internet of Things (IoT), encourages the birth of intelligent industries and smart ports with energy-saving and environmentally friendly technologies. However, the development of the Industrial Revolution 4.0 is expected to cause a decrease in the need for human resources (labour) and hurt social and economic aspects. Therefore, this study aims to analyse the improvement of HR quality to face the transformation of sea transportation to support national defence at sea. The research method used in this study is qualitative. Qualitative methods are used to formulate symptoms and information related to improving the quality of human resources to face the transformation of sea transportation to support national defence at sea. The phenomenon described in this research is the unoptimal quality of human resources in the maritime sector, especially in the port sector. The employee training system in the port sector still needs to be improved, and there is limited mastery and utilisation of information technology in the port sector. To solve these problems, efforts need to be made to improve the quality of human resources in the port sector, increase training for employees working in the port sector on an ongoing basis and optimise the mastery and use of information technology in the port sector. Improving the quality of human resources to face the transformation of sea transportation can provide benefits in the form of increased logistics and mobilisation capacity, increased maritime security surveillance, development of the domestic defence industry and operational flexibility.